(untitled) (Revista de Ciências Agroveterinárias, 2021)
Plant residues that remain in the soil of an integrated crop-livestock system constitute an important reserve of nutrients for crops in succession. The objective of this study was to evaluate the release of calcium (Ca), magnesium (Mg), and sulfur (S) from the decomposition of Urochloa brizantha cv. BRS Piatã pasture grass, fertilized with three different doses of nitrogen (N) and subjected to two different desiccation periods, prior to sowing a soybean crop. The experiment was conducted in Londrina, Paraná, between March 2016 and March 2018. Three different doses of N were applied to a pasture of U. brizantha cv. BRS Piatã (0, 150 and 300 kg N ha-1), forming three distinct paddocks. In each paddock, two different periods (60 and 15 days prior to sowing soybeans) for pasture desiccation were evaluated with four replications. Polynomial regression analysis was performed for the period after desiccation. Ca and S content in the U. brizantha straw did not vary over the course of decomposition, while magnesium content decreased, despite nitrogen fertilization and the desiccation periods. The amount of Ca released from U. brizantha straw by the end of the successive soybean cycle was approximately 15 kg ha-1, despite nitrogen fertilization and the desiccation periods. The amount of Mg released from U. brizantha straw by the end of the successive soybean cycle ranged from 10 to 15 kg ha-1, while the release of greater amounts tended to correspond with the presence of nitrogen fertilization in the pasture grass. The amount of S released from U. brizantha straw by the end of the successive soybean cycle ranged from 4 to 6 kg ha-1, while the release of lesser amounts tended to correspond with the presence of nitrogen fertilization in the pasture grass, despite the desiccation periods.